The Vitality of Interconnectedness: Vast’s Service Delivery Programme, First Alone, Then Together - Esfandiari, Mahshid; MacQueen, Frances (Refuge: Canada’s Journal on Refugees, 2000)
Work with survivors of torture requires a delicate balance of therapeutic approaches. This article presents the work of the Vancouver Association for the Survivors of Torture (VAST) by delving into some of VAST Therapeutic Principles of Care. It surveys the various therapeutic approaches embraced by VAST which help bridge the inside and outside world of survivors of torture. Among these approaches, bodywork plays a significant role in establishing this bridging. Most of all, this article emphasizes the need to respect the leads from the survivors themselves. Culturally appropriate and sensitive treatment approaches are central. All of these salient factors contribute to the holistic approach emphasized by VAST in order to join hands with survivors on their way to building a sense of interconnectedness and human vitality.